Exploring improved strategies for therapeutic studies and biological activities of novel zinc and indium phthalocyanines - Celep, Kevser; Atmaca, Goknur Yasa; Aydogmus, Pelin Demir; Eroglu, Kumsal; Gunkara, Omer Tahir; Giray, Gulay; Tollu, Gulsah; Ozdemir, Sadin; Erdogmus, Ali (ROYAL SOC CHEMISTRY, 2024)
This study investigates novel zinc and indium phthalocyanines with Schiff base and sulphur moieties, focusing on their potential for cancer therapy and antimicrobial applications. It explores the effectiveness of photochemical and sono-photochemical methods to enhance singlet oxygen production, which is crucial for photodynamic therapy. The synthesized complexes in this study demonstrated high singlet oxygen quantum yields, with D3 (ZnPc) and D4 (InPc) showing Phi Delta PDT values of 0.71 and 0.75, and Phi Delta SPDT values of 0.91 and 0.94, respectively. Furthermore, the evaluation for biological properties revealed that both D3 and D4 exhibit significant antidiabetic properties, DPPH radical scavenging activity, DNA cleavage, antimicrobial activity, biofilm inhibition, and microbial cell viability impacts, both with and without photodynamic therapy. Notably, D3 and D4 achieved antimicrobial cell viability inhibition rates of 84.67 +/- 4.67% and 98.32 +/- 5.96%, respectively, showcasing their effectiveness in photodynamic antimicrobial therapy. Overall, the study highlights the potential of these phthalocyanine complexes as advanced photosensitizers, with strong singlet oxygen generation and promising biological activities, paving the way for future therapeutic applications. This study investigates novel zinc and indium phthalocyanines with Schiff base and sulphur moieties, focusing on their potential for cancer therapy and antimicrobial applications.
Keywords: PHOTODYNAMIC THERAPY; RECENT PROGRESS; ANTIOXIDANT; PHOTOSENSITIZER; DNA; Chemistry